Three dimension (3D) hierarchical electrode (Au/rGO/CoPt3) for electrooxidation of ethanol in fuel cells - Huang, Kang (2020)
A highly efficient electrode for ethanol electrooxidation was successfully fabricated with the assistance of Nanoimprint Lithography (creation of 3D structure) and facile preparation method-electrodeposition. Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM), X-ray Diffraction (XRD) and Raman spectroscopy were used to characterize the electrodes obtained, which were further evaluated by Cyclic Voltammetry Potentiostat. It concludes that the electrocatalytic activity of the electrodes towards ethanol oxidation is promoted in the sequence of Au < Au/rGO < Au/rGO/CoPt3. The synergy effect of reduced GO and CoPt3 nanoparticle along with highly active gold thin layer forming 3D structure is responsible for the significant improvement of the catalysis.